Effects of sulfite treatment on the quality of black fungus. (15th August 2022) - Ren, Yichen; Huang, Jintao; Wang, Xingnan; Wang, Yaqin; Li, Hongcai; Yue, Tianli; Gao, Zhenpeng
Highlights: The black fungus treated with SO2 has bright color and is not easy to rot. The effect of SO2 on the color and content of black fungus were revealed. The correlation between SO2 and the composition of fungus were analyzed. The effect on the quality of black fungus was minimized. Abstract: In the present study, the color, total sugar, contents of soluble protein, total polyphenols, total flavonoids, and soluble vitamins, and other indicators of black fungus treated with sodium metabisulfite under different conditions were measured to evaluate the sensory and nutritional changes in black fungus after sulfite treatment. The results showed that use of sodium metabisulfite increased the lightness of black fungus, significantly increased the contents of total polyphenols and reducing sugars in the fungus ( p  < 0.05), increased the content of soluble protein, and decreased the content of total flavonoids. In addition, sodium metabisulfite destroyed vitamin C and B1 in black fungus. When the concentration of sodium metabisulfite was 0.5% and the soaking time 20 or 30 min, the color of black fungus improved markedly, and nutrients were not negatively affected. Therefore, the use of sodium metabisulfite improved the quality of fungus to a certain extent.